Multi-organ Immune-Related Adverse Event Is a Risk Factor of Immune Checkpoint Inhibitor-Associated Myocarditis in Cancer Patients: A Multi-center Study - Xie, Xiaohong; Wang, Liqiang; Li, Yingqing; Xu, Yan; Wu, Jianhui; Lin, Xinqing; Lin, Wen; Mai, Qicong; Chen, Zhanhong; Zhang, Jiexia; Xie, Zhanhong; Qin, Yinyin; et al. (Frontiers in Immunology, 2022)
Background and Objective: Immune checkpoint inhibitor (ICI)-associated myocarditis is a fatal immune-related adverse events (irAEs), which is prone to affecting multiple organ systems. Multi-organ irAEs have not been fully studied in ICI-associated myocarditis. Therefore, we aimed to explore the impact of multi-organ irAEs on ICI myocarditis in terms of clinical features, treatment, and prognosis. Methods: This was a retrospective study. The clinical data of ICI myocarditis patients were collected from 6 hospitals in China. The risk factors and characteristics of pure myocarditis and multi-organ irAEs were analyzed. The overall survival (OS) after myocarditis was analyzed and univariate and multivariate regression analysis were performed. Results: A total of 46 patients were analyzed in this study. Multi-organ irAEs were common (30/46, 65.2%) and prone to severe heart failure. The severe myocarditis was observed in 32 patients (69.6%). When myocarditis occurred, neutrophil to lymphocyte ratio, C-reactive protein, lactate dehydrogenase, interleukin (IL)-6, IL-10, creatine kinase, MB isoenzyme of creatine kinase, and brain natriuretic peptide increased from baseline, but absolute lymphocyte count decreased. Thymoma (B2/B3) was a risk factor for multi-organ irAEs. Heart failure and myocarditis were more severe in patients with multi-organ irAEs and require early corticosteroid therapy (<24 hours). Univariate analysis showed that age ≥ 60 years, myocarditis (grade 3-4), heart failure (grade 3-4), multi-organ irAEs, and severe myocarditis were associated with OS after myocarditis. After adjusting for other factors, heart failure (grade 3-4) was an independent risk factor for immune-related myocarditis (HR: 6.655, 95% CI: 1.539-28.770, p=0.011). Conclusion: Patients with ICI-associated myocarditis had multi-organ irAEs with a high incidence of severe myocarditis, mortality, and poor prognosis. Thymoma was prone to those patients with multiple organs involvement. Patients could benefit from early corticosteroid intervention. Heart failure (grade 3-4) was an independent risk factor for OS after myocarditis.